-5y-9+9y=6y+17

Simple and best practice solution for -5y-9+9y=6y+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5y-9+9y=6y+17 equation:


Simplifying
-5y + -9 + 9y = 6y + 17

Reorder the terms:
-9 + -5y + 9y = 6y + 17

Combine like terms: -5y + 9y = 4y
-9 + 4y = 6y + 17

Reorder the terms:
-9 + 4y = 17 + 6y

Solving
-9 + 4y = 17 + 6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6y' to each side of the equation.
-9 + 4y + -6y = 17 + 6y + -6y

Combine like terms: 4y + -6y = -2y
-9 + -2y = 17 + 6y + -6y

Combine like terms: 6y + -6y = 0
-9 + -2y = 17 + 0
-9 + -2y = 17

Add '9' to each side of the equation.
-9 + 9 + -2y = 17 + 9

Combine like terms: -9 + 9 = 0
0 + -2y = 17 + 9
-2y = 17 + 9

Combine like terms: 17 + 9 = 26
-2y = 26

Divide each side by '-2'.
y = -13

Simplifying
y = -13

See similar equations:

| 9x^2+30x+25x=0 | | 7p-10=-10+7p | | h(t)=-3t^2+36t | | 5e-3=17 | | 7+(x+4)=12 | | 3r+16=16-10r+13r | | 7(s-5)=421 | | 2n+3=3-7n | | 4-8+6b=4+6b | | 5x+104=10x-6 | | =5(9k+2)+8(3+4k) | | 4d-5(3d+10)=126 | | 0=12p+-48 | | -10-4v=-4v | | 0=-3t^2+36t-5 | | (-13)(-3)= | | 4x-x+2=3x-8 | | 0=-4w+4w | | 5x=32.50 | | -1-10q=-10q | | n+10+9n+3= | | -10-7m=10+3m | | 8x+48=-6x-8 | | 6.9x+5=5.9x | | -7g=-g-6g | | 3a^2-8a-16=0 | | 5x+3=9x-5 | | 3.5d=-7/8 | | =x+(4+3x)7 | | 2z=10z-8z | | -7/8/3.5= | | 9=19f+39-4f |

Equations solver categories